Survey Of Katabima Tembung School Training Model During The Covid-19 Pandemi Period Of Bandar Khalifah Village - Pangkey, Dikky Septian; Sari, Liliana Puspa (Journal of Football Research, 2025)
This study aims to determine the increase in learning outcomes of ball passing techniques using the inner foot in soccer games in the offline learning process during the Covid-19 pandemic period for X grade students of SMK Tunas Pelita Binjai for the 2020/2021 academic year. The subjects of this study were students of class X with a population of 1 class with a total of 30 students, in the form of teaching through learning media in pairs and groups. The media of this research is Classroom Action Research. After the data is collected and analyzed, the results of the analysis are obtained: (1) from the first test results in the first cycle, 26 students (65%) have reached the learning mastery level, while 4 students (35%) have not reached the learning mastery level. With an average value of 74.05. (2). From the learning outcomes test I. In Cycle II, 36 students (90%) have reached the learning mastery level, while 4 students (10%) have not reached the learning mastery level. With the average value of the second cycle of learning outcomes is 81.50. In this result, it can be seen that there is an increase in the average value of student learning outcomes from cycle I to cycle II, which is 12 students, an increase in classical completeness by 30%. Based on the results of data analysis, it can be said that through learning using the media in pairs and groups it increases. With the results of learning the technique of passing the ball using the inner foot of the soccer game in Class X Students of SMK Tunas Pelita Binjai for the 2020/2021 Academic Year.